2019
DOI: 10.18657/yonveek.491110
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Analysis Of Environmental Kuznets Curve Hypothesis: The Example Of Turkish Economy

Abstract: Bu çalışmasının temel amacı, ekonomik büyüme ve çevre kirliliği arasındaki ilişkiyi ters-U şeklinde açıklayan Çevresel Kuznets Eğrisi (ÇKE) hipotezinin geçerliliğini Türkiye ekonomisinde 1960-2014 dönemi itibariyle araştırmaktır. Bu amaçla karbon emisyonu, kişi başına reel gelir, kişi başına reel gelirin karesi, enerji tüketimi ve ticari dışa açıklık değişkenleri kullanılarak 3 farklı regresyon modeli oluşturulmuştur. Çalışmada değişkenlerin durağanlık derecelerinin tespiti için ADF, PP ve KPSS birim kök testl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Investigating the determinants of environmental degradation has increasingly drawn interest in the field of environmental economics. Most of these studies focus on validating the EKC hypothesis, which posits a link between economic growth and indicators of environmental degradation (Ghazouani, 2022; Çetin & Saygın, 2019; Ertugrul et al, 2016). The EKC proposes an inverted U‐shaped relationship between pollution and economic development.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Investigating the determinants of environmental degradation has increasingly drawn interest in the field of environmental economics. Most of these studies focus on validating the EKC hypothesis, which posits a link between economic growth and indicators of environmental degradation (Ghazouani, 2022; Çetin & Saygın, 2019; Ertugrul et al, 2016). The EKC proposes an inverted U‐shaped relationship between pollution and economic development.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The authors have surveyed the interaction degree between GDP and carbon emissions. Indeed, Kuznets (1955) hypnotized the inverted U-shaped assumption (Çetin & Saygin, 2019). The existing literature reported in Table 1 examines the bond between CO 2 -GDP growth for the EKC assumption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The environment theory can be defined as an inverted U‐shaped EKC. Many researchers used this approach for different areas with different variables to check the efficacy of growth and the environment (Çetin & Saygin, 2019; Demir et al, 2022). Rahman et al (2015) found a negative linkage among nonrenewable energy consumption and income growth.…”
Section: Introductionmentioning
confidence: 99%